(3JQLeI CQLhRI bUI HTQ HQgjR cGQ ef GdaGQSjI Edi GdYQHjIs - (3MSjf Hf eXdhes ((3GdbSWfWjfIs)
(3ChdgG (B:s
(3GSJeY eG Cbhd jG bGQj (B*** (3eG GdSHH aj fXGe CTYGQj , ghGfj CeQJ aj GdSGHb (B*** (3aj Yed bUJjf jG aGFbs
(3BNQgG (B:s
(3hJOHQ MbGFb GdCagGe (B*** (3hJHUQ ObGFb GdCbdGe , hGJb Gddg cj JfGd eGc (B*** (3hJMhR GdfYje aj CNQGcs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdCOHs